FAKTOR KEPEMIMPINAN DALAM EFEKTIVITAS PENGEMBANGAN USAHA KECIL MIKRO DAN MENENGAH - Angkawijaya, Tubagus Anis (Jurnal Sosial Politik Unla, 2020)
The development of Micro, Small and Medium Enterprises (MSMEs) in Indonesia is still not optimal. This problem is usually associated with one of the leadership variables at both the village / kelurahan and city / district levels. At the village level, the village head has an important role in advancing or retreating an MSME. The village head is assumed to have an effect on the effectiveness of MSME development in the country. This study took research in Neglasari Village, Banjaran District, Bandung Regency. The research question is how much influence the leadership of the village head has on the effectiveness of MSME development in Nrglasari Village? To analyze the research problem, theory is used as an analytical tool, namely leadership techniques, as suggested by Syafei (2013: 41-46), including persuasive techniques, communicative techniques, facilities techniques, motivation techniques, exemplary techniques. The theory of effectiveness uses the theory of Steers (1985: 4-7) which consists of an understanding of goal optimization, a systematic perspective, and an emphasis on human behavior in an organizational structure. Based on the theoretical approach, the hypothesis proposed is: "The magnitude of the influence of the village head leadership on the effectiveness of the development of micro, small and medium enterprises in Nrglasari Village, Banjaran District, Bandung Regency is determined by the implementation of the dimensions of persuasive techniques, communicative techniques, facility techniques, motivational techniques, techniques. exemplary. "